Towards a semantic-driven and scalable publish/subscribe framework. (1st January 2013) - Chaabane, Amina; Diop, Codé; Louati, Wassef; Jmaiel, Mohamed; Gómez-Montalvo, Jorge; Exposito, Ernesto
Heterogeneous networks, including personal, home and collaborative enterprise networks are aimed at interconnecting diverse communities of users. In the case of large communities of mobile, distributed and collaborating users sharing their multimedia content, scalable and semantic approaches are needed to facilitate the efficient publication and discovery of data. In this work, we propose an approach aimed at efficiently providing the required functionalities for dynamically managing the resources and the multimedia content of interconnected home networks, as well as providing the required community sharing capabilities. Our solution consists in combining the benefits of both ontologies and peer-to-peer approaches, by taking advantage of the semantic capabilities of ontologies at local domain level and the scalable P2P solutions at inter-domains level. Our proposed framework is founded on a new architecture based on peer-to-peer event-based communication system and using mainly a home box entity based on a global multimedia ontology. This domain ontology allows publishers and subscribers to use a common semantic space to characterise production and consumption of resources and services. Our approach can also be applied for similar large interconnected systems scenarios such as topic discovery with JNDI and service exchange with UDDI.